1999
DOI: 10.1016/s1146-609x(99)00137-x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, dynamics and production of Hydrobia ulvae (Pennant) (Mollusca: Prosobranchia) along an eutrophication gradient in the Mondego estuary (Portugal)

Abstract: -Eutrophication in the Mondego estuary gave rise to qualitative changes in the benthic community, involving the replacement of eelgrass, Zostera noltii, by green algae such as Enteromorpha spp. and Ulva sp. It seems reasonable to assume that, through time, such changes may determine a selected new trophic structure. Hydrobia ulvae, a dominant species in terms of abundance and biomass, was studied with regard to life history, population dynamics and productivity in relation to changing environmental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 32 publications
6
99
1
1
Order By: Relevance
“…Macroalgal blooms of Ulva spp. have regularly been observed in the Mondego over the last 20 years (Flindt et al, 1997;Marques et al, 1997Marques et al, , 2003Lillebø et al, 1999;Pardal et al, 2000Pardal et al, , 2004Martins et al, 2001;Dolbeth et al, 2003;Cardoso et al, 2004). Nevertheless, such macroalgal blooms may not occur in exceptionally rainy years.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Macroalgal blooms of Ulva spp. have regularly been observed in the Mondego over the last 20 years (Flindt et al, 1997;Marques et al, 1997Marques et al, , 2003Lillebø et al, 1999;Pardal et al, 2000Pardal et al, , 2004Martins et al, 2001;Dolbeth et al, 2003;Cardoso et al, 2004). Nevertheless, such macroalgal blooms may not occur in exceptionally rainy years.…”
Section: Study Areamentioning
confidence: 99%
“…Sampling was conducted in three areas in the southern arm of the Mondego estuary that represent different environmental situations along a spatial gradient of eutrophication Lillebø et al, 1999;Pardal et al, 2000Pardal et al, , 2004Dolbeth et al, 2003;Cardoso et al, 2004;Neto, 2004) (Fig. 1): (a) a non-eutrophic area (Zostera noltii Hornem beds), (b) an intermediate eutrophic area (Z. noltii absent, although residual roots can still be found in the sediment, and the occasional formation of abundant macroalgae mats) and (c) a strongly eutrophic area (macrophyte community totally absent for at least a decade and strong, regularly occurring, blooms of Ulva spp.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The common mud snail Hydrobia ulvae is a widespread deposit feeder at fine-grained sediments on European intertidal flats and an evaluation of the effect of this species on the erodibility of the bed is therefore of major importance. The snail may occur in densities of up to about 300 000 individuals m À 2 (Blanchard et al, 1997;Austen et al, 1999;Jensen, 1992;Lillebø et al, 1999). Some studies (Blanchard et al, 1997;Andersen, 2001a) have indicated that H. ulvae increase the erodibility of their substrata.…”
Section: Introductionmentioning
confidence: 99%
“…Microcosmos experiments have suggested that, even at low densities, nematodes can have a significant structuring top-down influence on the bacteria growing on the cordgrass leaves detritus (DeMesel et al, 2004). Macrofauna may also feed directly on bacteria, and species such as Hydrobia ulvae, through their feeding activities on leaf surfaces (Barnes & Hughes, 1988;Lillebø et al, 1999b), might contribute to the stimulation of microbial activity. Moreover, it has been shown that, in the presence of meiofauna, polychaetes can incorporate significantly more carbon from Zostera detritus (Tenore et al, 1977in Valiela, 1995.…”
Section: Discussionmentioning
confidence: 99%